2019
DOI: 10.1186/s12889-019-8003-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between perceptions of the neighbourhood environment and physical activity in adolescents: evidence from the Olympic Regeneration in East London (ORiEL) study

Abstract: BackgroundMost UK adolescents do not achieve recommended levels of physical activity. Previous studies suggested that perceptions of the neighbourhood environment could contribute to explain differences in physical activity behaviours. We aimed to examine whether five measures of perceptions – perceived bus stop proximity, traffic safety, street connectivity, enjoyment of the neighbourhood for walking/cycling, and personal safety – were longitudinally associated with common forms of physical activity, namely w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Owing to the skewed distribution of the total time spent on each form of PA and to the fact that no adequate transformation could be found, the four outcome variables were dichotomised as ‘activity reported at least once’ versus not. 30 31…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the skewed distribution of the total time spent on each form of PA and to the fact that no adequate transformation could be found, the four outcome variables were dichotomised as ‘activity reported at least once’ versus not. 30 31…”
Section: Methodsmentioning
confidence: 99%
“…The adjusted models included gender, ethnicity (White UK, White Mixed, Indian, Pakistani, Bangladeshi, Black Caribbean, Black African or Other), household composition (both parents vs not), time lived in the neighbourhood (≤5 years vs > 5), free-school meal status, family affluence (three categories from the revised Family Affluence Scale II) and the presence of health condition (none vs 1+; from the following conditions: mobility problems, longstanding illness, anaemia, asthma, diabetes, Chronic Fatigue Syndrome, hay fever, hearing and eyesight problems). 30 31…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, environmental perceptions are complementary predictors of physical activity behavior (Orstad et al, 2017). Berger et al (2019) show that younger adolescents' environmental perceptions and changes in these perceptions do not consistently predict their interest in physical activity.…”
Section: Relationships Among Perception Of Sports Environment Expecta...mentioning
confidence: 99%
“…In addition, low neighbourhood perceived safety has been associated with reduced physical activity in 11-16 year olds in Chicago (Molnar et al ., 2004). A UK study, using longitudinal data from East London, reported that adolescents’ perceptions of their neighbourhood safety was not associated with self-reported physical activity (Berger et al ., 2019). Similarly, research in the US found that girls, but not boys, exposed to high crime neighbourhoods (measured with census tract-level data on crime reports) had lower odds (OR = 0.74, 95% CI = 0.59-0.92) of engaging in moderate-to-vigorous physical activity (Pia Chaparro, Bilfield and Theall, 2019).…”
Section: Introductionmentioning
confidence: 99%